Juridical Analysis of Penalty Clauses in Construction Contracts Based on Bpk Audits for State-Owned Developer Companies: A Case Study of Housing Project C in Company P - Resi Aseanto; Bondan Christiandinata (Journal of Social Research, 2026)
This study examines the juridical implications of penalty clauses in State-Owned Enterprise (SOE) construction contracts through a case study of Housing Project C between Company P and Company M. The research addresses the complex intersection of private law, public audit mechanisms, and judicial review in SOE contract enforcement. Using normative legal research methodology, this study analyzes the construction contract, BPK (Supreme Audit Institution) audit findings, and Supreme Court decisions to understand the legal position and enforceability of penalty clauses in SOE construction contracts. The findings reveal that while penalty clauses in SOE construction contracts are normatively valid under civil law provisions, their enforcement is subject to significant limitations arising from the hybrid legal character of SOEs. The BPK audit findings, which identified potential state losses due to project delays, compelled Company P to enforce contractual penalties as part of accountability and Good Corporate Governance principles. However, the Supreme Court's decision limited the maximum penalty to 2% instead of the contractually stipulated 5%, demonstrating that the principle of pacta sunt servanda is not applied absolutely in SOE construction contracts. This study concludes that SOE construction contracts operate at the intersection of three legal regimes: private law (contractual freedom), public law (state audit oversight), and judicial law (court interpretation). The Supreme Court's emphasis on fairness and proportionality principles over strict contractual interpretation reflects the unique legal challenges facing SOE contracts. These findings indicate that SOEs cannot rely solely on textual contract formulations but must consider judicial interpretation possibilities, fairness principles, and public accountability requirements when drafting construction contracts. The research contributes to legal theory development in contract law, construction law, and SOE business law, while providing practical recommendations for SOEs to draft more robust, audit-resistant construction contracts with greater legal certainty. The study recommends an integrative legal approach in designing SOE construction contracts that balances private contractual principles with public law obligations and anticipates judicial review considerations.